Incredible world of biotechnology - Singh M.P.; Verma V.; Singh A.K. (My University, 2025)
The term Biotechnology is "any technological application that uses biological systems, living organisms or their derivatives, to make or modify products or processes for specific use". The humanity is facing a colossal problem due to population explosion and over exploitation of natural resources. Biotechnology is one of the most cutting edge technologies which have the prospective to address some of the world's paramount challenges, such as feeding a rising population and offering novel alternatives to our limited natural resources. The ultimate objective of biotechnology is to meet human requirements in order to improve our quality of life. Because of the progression of comprehensive research and development, the prominence of biotechnology has come to existence. It is widely used in agriculture, medicine, engineering, science and technology, and other form of applications and can be panacea for the problems of mankind. Apart from that research in the field of transgenic animals and plants, use of various microorganisms' derived products in microbiology has changed the way of the interaction of biotic and abiotic components of the earth. For the immensely diverse field and the development it surely is observed that this science is worth to be called as incredible biotechnology. © 2017 by Nova Science Publishers, Inc. All rights reserved.